Low Energy Architecture and Low Carbon Cities Exploring Links, Scales, and Environmental Impacts - Pomponi, Francesco; D'Amico, Bernardino (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The built environment is at a turning point. With projected trends in population growth and urbanization, global demand for new floor area is expected to rise sharply. This will put unprecedented pressure on the availability of natural resources and incur greenhouse gas emissions and energy demand. Such environmental stressors risk driving the world away from the UN Sustainable Development Goals, but equally represent an opportunity for just sustainability transitions. The contents of this book aim to address some of these grand challenges from a multi-disciplinary perspective. Low-energy architecture, low-carbon cities and the often-forgotten sustainability of refugee settlements are some of the themes dealt with by the authors.